Randomized Clinical Trial of First‐Line Genome Sequencing in Pediatric White Matter Disorders. Issue 2 (9th June 2020) - Vanderver, Adeline; Bernard, Geneviève; Helman, Guy; Sherbini, Omar; Boeck, Ryan; Cohn, Jeffrey; Collins, Abigail; Demarest, Scott; Dobbins, Katherine; Emrick, Lisa; Fraser, Jamie L.; Masser‐Frye, Diane; et al.
Abstract : Objective: Genome sequencing (GS) is promising for unsolved leukodystrophies, but its efficacy has not been prospectively studied. Methods: A prospective time‐delayed crossover design trial of GS to assess the efficacy of GS as a first‐line diagnostic tool for genetic white matter disorders took place between December 1, 2015 and September 27, 2017. Patients were randomized to receive GS immediately with concurrent standard of care (SoC) testing, or to receive SoC testing for 4 months followed by GS. Results: Thirty‐four individuals were assessed at interim review. The genetic origin of 2 patient's leukoencephalopathy was resolved before randomization. Nine patients were stratified to the immediate intervention group and 23 patients to the delayed‐GS arm. The efficacy of GS was significant relative to SoC in the immediate (5/9 [56%] vs 0/9 [0%]; Wild–Seber, p < 0.005) and delayed (control) arms (14/23 [61%] vs 5/23 [22%]; Wild–Seber, p < 0.005). The time to diagnosis was significantly shorter in the immediate‐GS group (log‐rank test, p = 0.04). The overall diagnostic efficacy of combined GS and SoC approaches was 26 of 34 (76.5%, 95% confidence interval = 58.8–89.3%) in <4 months, greater than historical norms of <50% over 5 years. Owing to loss of clinical equipoise, the trial design was altered to a single‐arm observational study. Interpretation: In this study, first‐line GS provided earlier and greater diagnostic efficacy in white matter disorders. We provide an evidence‐based diagnostic testing algorithm to enable appropriate clinical GS utilization in this population. ANN NEUROL 2020;88:264–273.